(untitled) (Communications in Computational Physics, 2020)
Staining algorithms based on two-way wave equation migration methods have been applied to improve the signal-to-noise ratio (SNR) of poorly illuminated structures such as those in subsalt zones. In regular staining algorithms, when a source wavefield reaches the stained area that is associated with the target structures, a new wavefield called stained wavefield is excited, and this stained wavefield forward extrapolates synchronously with the real source wavefield. The forward-extrapolated stained and real source wavefields are cross-correlated with the backward-extrapolated receiver wavefield, and we obtain the stained and the real reverse time migration (RTM) images. The staining algorithms for RTM can suppress the noise of non-target regions and obtain high SNR images of the target structures. Whereas RTM methods are limited by the low computational efficiency and SNR, by contrast, one-way wave equation migration (OWEM) methods have the advantages of high efficiency and no interference from multiples. Thus, we developed a new staining method based on the generalised screen propagator (GSP) as a case of OWEM methods for subsalt imaging. Furthermore, a new stained wavefield called stained receiver wavefield is proposed here, forming two new staining strategies for seismic imaging, in which forward-propagated source and backward-propagated receiver wavefields can be conveniently selected to be stained at the stained area. Numerical experiments demonstrated that this staining GSP method is more effective in improving the SNR of subsalt structures compared to conventional GSP migration and RTM methods; moreover, these new staining strategies as applied to the OWEM methods can greatly improve the SNR of weakly illuminated structures in subsalt zones, in comparison with regular staining algorithms for one-way methods.